Nausea and vomiting in pregnant adolescents: impact on health-related quality of life - Yılmaz, Elif; Tokgöz, Betül; Soysal, Çağanay; Şahin Aker, Seda; Küçüközkan, Tuncay (The European Research Journal, 2018)
Objective: To determine the impact of the presence and severity of nause and vomiting in pregnancy (NVP) on health-related quality of life in pregnant adolescents. Methods: Two hundred and fifty adolescent pregnant women were included in this study. The Rhodes test was performed to determine the severity of nausea and vomiting, and the self-reported 36-Item Short Form Survey (SF-36) Scale was administered. The study was divided into four groups according to nausea severity (no, mild, moderate, severe) groups and SF-36 scores were compared among the groups. Results: Of the 250 pregnant women included in the study, 74.5% of women reported NVP. Low scores on the SF-36 were found for all items with increasing severity of NVP, with the lowest scores in the severe NVP group and the highest scores in the group with no NVP (p = 0.001). Multivariable analyses showed that severity of NVP was the most important factor for both the physical (PCS) and mental component summary (MCS) scales. The number of living children was significantly associated with lower PCS scores and being unable to share problems with spouse/relatives was correlated with lower MCS scores. Conclusion: The negative impact of nausea and vomiting on health-related quality of life, emphasises the importance of psychological support and optimal management of NVP in pregnant adolescents.